2021
DOI: 10.1038/s41388-021-01711-x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A kinase oncogenic signaling mediates TGF-β-induced triple-negative breast cancer plasticity and chemoresistance

Abstract: Triple-negative breast cancer (TNBCs) account for 15–20% of all breast cancers and represent the most aggressive subtype of this malignancy. Early tumor relapse and progression are linked to the enrichment of a sub-fraction of cancer cells, termed breast tumor-initiating cells (BTICs), that undergo epithelial to mesenchymal transition (EMT) and typically exhibit a basal-like CD44high/CD24low and/or ALDH1high phenotype with critical cancer stem-like features such as high self-renewal capacity and intrinsic (de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 51 publications
(31 reference statements)
0
28
0
Order By: Relevance
“…Blocking the b-catenin pathway and inhibiting AURKA activity at the same time may enhance antitumor response in adrenocortical cancer (25). AURKA was essential for mediating TGF-beta induced plasticity and chemoresistance in triple-negative breast cancer (26). Liu (27) found that knockdown of AURKA could lead to increased radiotherapy efficacy in human colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the b-catenin pathway and inhibiting AURKA activity at the same time may enhance antitumor response in adrenocortical cancer (25). AURKA was essential for mediating TGF-beta induced plasticity and chemoresistance in triple-negative breast cancer (26). Liu (27) found that knockdown of AURKA could lead to increased radiotherapy efficacy in human colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β signaling plays a crucial role in various tumors, including GBC [ 23 , 24 ]. It has been reported that TGF-β can activate SMAD2 [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing issue is whether such primed cells are already present in healthy or premalignant epidermal cells as a key factor that engenders the refractoriness of tumor cells to chemotherapies. Other studies also prove that TGF-β-induced EMT is associated with drug resistance in carcinoma [104][105][106]. Thus, targeting TGF-β-related EMT in carcinoma could help to improve the drug efficiency and partially solve resistance issues.…”
Section: Tgf-β Signaling In Carcinoma Plasticitymentioning
confidence: 91%